UPAYA MENINGKATKAN HASIL BELAJAR SISWA MENGGUNAKAN MODEL PEMBELAJARAN FISH BOWL PADA MATERI KETENAGAKERJAAN - Sigit Marteja (UNIVERSITAS MUHAMMADIYAH METRO, 2022)
This research is entitled efforts to improve student learning outcomes using the fish bowl model in employment material for the 2021/2022 school year. 2021/2022 and this research aims to: find out the increase in student learning outcomes using the fish bowl learning model, research subjects 36 students. Retrieval of data using the method of observation, written test. The study was conducted in 2 cycles: the stages of planning, implementing, acting, observing, and reflecting. The results of the study increased student learning outcomes in the pre-cycle results of students who completed 17 students (45.83%), students who had not completed 19 students (54 .16%), the first cycle of students who completed 22 (58.33%)., students who have not completed 14 (41.66%), in the second cycle of students completed 35 (95.83%), and 1 student (4, 16%) have not been completed. Increased student activity from cycle I to cycle II in a better direction. This was shown by an increase in student learning activity from the first cycle of 78.02% to 95.35% in the second cycle. Keywords: hasil belajar, model fish bowl, ketenagakerjaan